The Diagnosis and Management of Congenital Hemophilia - Carcao, Manuel D. (Seminars in Thrombosis and Hemostasis, 2012)
Hemophilia is the most common, severe, inherited bleeding disorder recognized in humans and makes up the largest proportion of patients followed in most bleeding disorders' clinics. Persons with hemophilia have a life-long bleeding tendency that roughly correlates to their endogenous coagulant factor VIII (FVIII) or factor IX (FIX) level (FVIII:C and FIX:C). The hallmark of bleeding in severe hemophilia is musculoskeletal bleeds (soft tissue, muscle and joint bleeds) but persons with hemophilia are also prone to other bleeds including intracranial bleeds. The neonatal period is a particularly vulnerable period for persons with severe hemophilia. Diagnosing hemophilia is mainly based on measuring FVIII:C and FIX:C levels and on distinguishing hemophilia from other conditions that can cause a low FVIII:C or FIX:C level. Management involves preventing bleeds and rapidly treating those that occur. Bleed prevention in severe hemophilia can be accomplished by avoiding high-risk activities, taking appropriate precautions and early commencement of life-long prophylaxis. With proper management, persons with severe hemophilia can now live an essentially normal life. The development of an inhibitor does however complicate management. This review will summarize the very complex and multifaceted aspects of diagnosing and managing persons with hemophilia.
Keywords: hemophilia; diagnosis; management; prophylaxis